2022
DOI: 10.1038/s41586-022-05522-2
|View full text |Cite
|
Sign up to set email alerts
|

The WHO estimates of excess mortality associated with the COVID-19 pandemic

Abstract: The World Health Organization has a mandate to compile and disseminate statistics on mortality, and we have been tracking the progression of the COVID-19 pandemic since the beginning of 20201. Reported statistics on COVID-19 mortality are problematic for many countries owing to variations in testing access, differential diagnostic capacity and inconsistent certification of COVID-19 as cause of death. Beyond what is directly attributable to it, the pandemic has caused extensive collateral damage that has led to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
303
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(420 citation statements)
references
References 20 publications
(19 reference statements)
14
303
2
6
Order By: Relevance
“…E.g. in 2020-2021, WHO estimates 6,288 excess deaths in South Korea (32), Economist estimates 7,558 excess deaths (33), while our calculations (using 2017-2019 as baseline) shows a death deficit (34).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…E.g. in 2020-2021, WHO estimates 6,288 excess deaths in South Korea (32), Economist estimates 7,558 excess deaths (33), while our calculations (using 2017-2019 as baseline) shows a death deficit (34).…”
Section: Discussionmentioning
confidence: 58%
“…E.g. in 2020-2021, WHO estimates 6,288 excess deaths in South Korea (36), Economist estimates 7,558 excess deaths (37), while our calculations (using 2017-2019 as baseline) shows a death deficit (38). Economist projects 54,352 excess deaths as of November 14, 2022 (37), while our calculations based on age-stratified data (available until summer 2022) and using 2017-2019 as a baseline suggest a persistent death deficit until the summer of 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study by the World Health Organization showed that the number of excess deaths during the COVID-19 period might be largely underestimated, with 2.74-fold more cases than what has been reported. 13) To deliver critical information during the pandemic and facilitate scientific advancements against COVID-19, most academic journals have conducted fast-track peer-reviewing and prioritized the publication of articles on the disease. Consequently, the volume of articles in the field has been massive and the impact factors of major medical journals have been affected by substantial changes from such an irregular pattern of publication.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Furthermore, a recent study by the World Health Organization showed that the number of excess deaths during the COVID-19 period might be largely underestimated, with 2.74-fold more cases than what has been reported. 13 )…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Figure 1 | Country income level and estimated excess deaths from COVID-19. Msemburi et al1 estimated the number of excess deaths that occurred in every country in the world in 2020 and 2021. Here, countries are grouped according to their income level (high, upper middle and so on).…”
mentioning
confidence: 99%